ANALYSIS OF FORMING PSYCHOLOGICAL TERMS IN ENGLISH - Jovbo‘riyeva, Saodat (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article studies formation ways of psychological terms in English language. The author analyzed the formation of psychological terms in the English language by affixation, word acquisition and compounding ways. Also the author gives examples of psychological terms.